THE MANAGEMENT IMPLEMENTATION OF CHARACTER VALUE AT JUNIOR HIGH SCHOOL - Sipiana, Sisilia; Suriansyah, Ahmad; Effendi , Rustam (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
This study aims to plan and evaluate the implementation of character values. It was carried out in Santa Angela Banjarmasin and Sanjaya Banjarbaru Junior High Schools using the qualitative, empirical, and multi-site design approaches. Furthermore, the research subjects comprise of principal, vice-principals, teachers, students, committees, and the school Foundation. Data were collected through observation, in-depth interviews, and documentation.  Analysis of the data collected was conducted through reduction, conclusion, presentation, and verification. The results of the study, therefore, aimed at the implementation of character values to students through planning, organizing, implementing, and evaluating. These stages are appropriately carried out in school management, implemented in its curriculum, with results developed into character values.